2019
DOI: 10.21608/ejh.2019.11113.1106
|View full text |Cite
|
Sign up to set email alerts
|

The possible radioprotective effects of vitamin E, Nigella sativa oil, and melatonin against X-ray induced early acute changes in cerebral and cerebellar cortices in Albino rats: Histological and Immunohistochemical study.

Abstract: Background: Radiation induced brain and cerebellum injury is common in patients receiving radiotherapy for head and neck tumors. Administration of antioxidants before radiation as vitamin E, nigella sativa oil and melatonin could be valuable in limiting this injury. Material and Methods: 40 rats were divided into five different groups. Group Ι: served as the control group and subdivided into 4subgroups. subroup Ia: negative control, subgroup Ib: animals received vitamin E only (300 mg/kg orally once, subgroup … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
(68 reference statements)
3
2
0
Order By: Relevance
“…Vitamin E treatment also decreased the inflammatory infiltrate in the underlying submucosa with absence of inflammation with the high vitamin E dose (500 mg/Kg). Similar result was obtained by Nor-Eldin and Elsayed [ 11 ] who found that 300 mg/Kg vitamin E provided a protection for brain and cerebellum against whole body irradiation at eight Gy. Similarly, Saleh et al [ 26 ] found that vitamin E (40 mg/Kg/day) reduced the cytotoxic effect of cyclophosphamide with regard to rats’ tongues.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Vitamin E treatment also decreased the inflammatory infiltrate in the underlying submucosa with absence of inflammation with the high vitamin E dose (500 mg/Kg). Similar result was obtained by Nor-Eldin and Elsayed [ 11 ] who found that 300 mg/Kg vitamin E provided a protection for brain and cerebellum against whole body irradiation at eight Gy. Similarly, Saleh et al [ 26 ] found that vitamin E (40 mg/Kg/day) reduced the cytotoxic effect of cyclophosphamide with regard to rats’ tongues.…”
Section: Discussionsupporting
confidence: 89%
“…Rats were randomly divided into five groups (n = 7); group C: negative control (Neither irradiation nor treatment was given), group R: rats were subjected to localized gamma-irradiation only, however for groups R + 300 VE, R + 360 VE and R + 500 VE: rats were subjected to localized gamma-irradiation followed by 300, 360 and 500 mg/Kg/day oral vitamin E for 7 days, respectively [9][10][11].…”
Section: Groupingmentioning
confidence: 99%
“…Moreover, it significantly decreased TGF-β expression compared to irradiated glands. These results were parallel to those obtained by Nor-Eldin and Elsayed [ 32 ], where administration of NSO improved the cerebral and cerebellar changes induced by exposure to X-ray (8 Gy) with a significant decrease in the number of GFAP-positive astrocytes. Likewise, administration of NSO provided partial protection and improvement of histopathological alterations of parotid gland subjected to fenitrothion intoxication [ 33 ].…”
Section: Discussionsupporting
confidence: 87%
“…These results were parallel to those obtained by Nor-Eldin and Elsayed [32] , where administration of NSO improved the cerebral and cerebellar changes induced by exposure to X-ray (8 Gy) with a signi cant decrease in the number of GFAP-positive astrocytes. Likewise, administration of NSO provided partial protection and improvement of histopathological alterations of parotid gland subjected to fenitrothion intoxication [33] .…”
Section: Discussionsupporting
confidence: 86%